1986
DOI: 10.1055/s-0038-1661606
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Comparison of Fibrinolytic Activity of Plasminogen Activators Using a Thrombelastographic Method: In Vivo Evaluation of the B-Chain-Streptokinase Complex in the Dog Model Using Pre-Titered Doses

Abstract: SummaryThrombelastography was used to quantitatively compare the clot-lysing efficiency of 6 different plasminogen activators, using human whole blood, pooled normal plasma, and platelet rich plasma. The activators compared were the B-chain-streptokinase complex, the plasmin-streptokinase complex, the mini-plasmino-gen-streptokinase complex, tissue plasminogen activator, streptokinase, and urokinase. The most efficient activator found was the B-chain-streptokinase complex. This complex was 4.0 times more effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…27 Recently, Summaria et al showed a progressive decrease in whole blood clot lysis time when incremental doses of the plasminogen activator, β-chain-streptokinase, were added to whole blood. 28 Streptokinase that was given to patients with thrombotic conditions showed similar changes in whole blood clot lysis time.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…27 Recently, Summaria et al showed a progressive decrease in whole blood clot lysis time when incremental doses of the plasminogen activator, β-chain-streptokinase, were added to whole blood. 28 Streptokinase that was given to patients with thrombotic conditions showed similar changes in whole blood clot lysis time.…”
Section: Discussionmentioning
confidence: 94%
“…28 Streptokinase that was given to patients with thrombotic conditions showed similar changes in whole blood clot lysis time.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 94%
“…In a canine model with controlled levels of streptokinase, TEG could detect clot dissolution before changes were noted in plasma fibrinogen or plasminogen levels (52). The activated clotting time, PT, and aPTT do not provide information about fibrinolysis (they measure aspects of coagulation only up to the formation of the fibrin clot) (16).…”
Section: Discussionmentioning
confidence: 99%
“…29 In dogs with experimentally induced thrombus formation, there was good agreement between TEG fibrinolysis variables, FDPs, thrombus size, and local blood flow at the site of the thrombus after fibrinolytic therapy. 36 However, in a recent case series of dogs with disseminated intravascular coagulation (DIC) and subsequent secondary fibrinolysis, there was no association between D-dimer concentration and increased rhTF-Haemoscope TEG fibrinolytic variables. 29 Similar results were reported in a study in which human patients with severe sepsis, with or without overt DIC, had increased D-dimer concentration with no concurrent increase in ROTEM fibrinolytic markers using TF activation.…”
Section: Teg Variables and Correlation With Routine Coagulation Assaysmentioning
confidence: 99%